2017
DOI: 10.1097/aog.0000000000001836
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy Interval After Termination of Pregnancy and the Risks of Adverse Outcomes in Subsequent Birth

Abstract: Slightly but significantly increased estimated risk of preterm delivery in subsequent pregnancy was seen when the interpregnancy interval after termination of pregnancy was less than 6 months. These data emphasize the need for prompt initiation of effective contraception after termination and enable counseling the patient for optimal conception interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…For both IVF and non-IVF deliveries following a non-live pregnancy outcome, short IPI was not associated with increased risk for adverse perinatal outcomes. These findings are consistent with some (4,8,9), but not all (10,11), studies. California birth certificate data showed slightly protective associations between short IPIs following a non-live pregnancy (4) outcome and PTB, similar to our findings for the non-IVF population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For both IVF and non-IVF deliveries following a non-live pregnancy outcome, short IPI was not associated with increased risk for adverse perinatal outcomes. These findings are consistent with some (4,8,9), but not all (10,11), studies. California birth certificate data showed slightly protective associations between short IPIs following a non-live pregnancy (4) outcome and PTB, similar to our findings for the non-IVF population.…”
Section: Discussionsupporting
confidence: 93%
“…California birth certificate data showed slightly protective associations between short IPIs following a non-live pregnancy (4) outcome and PTB, similar to our findings for the non-IVF population. In contrast, Finnish population-based data showed that PTB risk was higher with short IPI following pregnancy terminations (11). For those planning an IVF pregnancy after a pregnancy loss, the data from the current study did not suggest a significant increase in risk for the adverse outcomes when pregnancies are less than a year apart.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5 Some studies have shown obstetric outcomes as an independent determining factor in the incidence of adolescent repeated pregnancies, observing longer inter-pregnancy intervals among women who experienced prenatal and/ or childbirth complications. 7 However, it has been also observed the opposite, as many women with history of poor outcomes during their first pregnancy tend to have a rapid repeat pregnancy, with a less than 12 months between deliveries interval. 8 It appears that, to reduce adolescent pregnancy rates in developed and developing countries, actions should be focused on a multifaceted and interdisciplinary management that address not only the risk factors and risk-behavior, but also aims for social and cultural factors that influence young people's decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from developed countries showed that the risk of developing adverse neonatal outcomes to be higher in pregnancies with short IPI (10)(11)(12). Other reports from developed countries showed an increased risk of developing preterm birth and LBW eventhough they show insigni cant association for other adverse neonatal outcomes (13). Similarly the effect of short IPI on adverse neonatal outcomes among developing countries was also supported by many literatures (14,15).…”
Section: Introductionmentioning
confidence: 71%